Factors influencing low motivation of PKWU teachers and organizational climate in the participation of MGMP - Siregar, Rosmala Sari Dewi; Amir, M. Taufiq (Indonesian Journal of Educational Development (IJED), 2025)
This study aimed to analyze the factors contributing to the low motivation and organizational climate of the Subject Teacher Consultation Forum (MGMP) for Handicrafts and Entrepreneurship (PKWu) regarding teacher participation in activities within the DKI Jakarta area. Using a descriptive qualitative method, data were collected through both in-person and online interviews. The primary respondents consisted of five teachers from five regions in DKI Jakarta, whose motivation levels were assessed. The selection of these teachers as respondents was based on their teaching experience and their role as core administrators of the MGMP. Research result, showed that teachers' motivation to participate in MGMP activities was largely influenced by the achievement motive and the expectation of recognition. Most teachers were willing to forgo incentives but expected acknowledgment for their contributions. On the other hand, the organizational climate was assessed as relatively positive, as the management was willing to take risks regarding work programs without significant conflicts, although differences of opinion could be effectively resolved. However, several weaknesses were identified, particularly within the structural elements of the organization. The MGMP lacked formal statutes and bylaws, the administrators demonstrated limited accountability, there was no incentive system in place, and only one region had a work program serving as the organization's standard operating procedure. These factors served as major obstacles to develop a more effective organizational climate. The need for policy involvement from stakeholders to establish regulations requiring teachers to be assigned to the PKWu subject for a minimum of two years. This aligned with the study's findings that external factors, particularly from superiors, influenced individuals' willingness to engage in self-development, especially in MGMP activities.